2021
DOI: 10.1186/s12909-021-02898-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of teaching integrated course of physical examination and radiological anatomy in practical limb anatomy on medical students’ learning outcomes

Abstract: Background In the last few decades, the need to change the curriculum of basic medical science has been further emphasized. The purpose of this study was to evaluate the effects of teaching integrated course of physical examination and radiological anatomy in practical limb anatomy on medical students’ learning outcomes. Methods This was an experimental study. Medical students (of the 4th semester of medical education) were divided into interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[ 28 ] For instance, a recent study assessing the effect of integrated teaching-clinical and theoretical-in the learning of undergraduate students, reported improved acquisition, retention, and applicability of knowledge along with greater student satisfaction. [ 29 ] In another study, enhancing the course material using multimedia materials, improved student engagement and attitudes regarding the course materials. [ 30 ] Another study established that presenting learning materials in a variety of representation forms/channels (voice, visuals, and screen text/labels) results in superior outcomes to solely speech or simultaneous presentation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] For instance, a recent study assessing the effect of integrated teaching-clinical and theoretical-in the learning of undergraduate students, reported improved acquisition, retention, and applicability of knowledge along with greater student satisfaction. [ 29 ] In another study, enhancing the course material using multimedia materials, improved student engagement and attitudes regarding the course materials. [ 30 ] Another study established that presenting learning materials in a variety of representation forms/channels (voice, visuals, and screen text/labels) results in superior outcomes to solely speech or simultaneous presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Human Anatomy courses in nursing programs often require many faculty members to adequately cover a broad range of course content, potentially leading to challenges due to a single teaching method and a heavy teaching load. Moreover, conventional Human Anatomy courses may fail to inspire enthusiasm among students and provide them with sufficient practical preparation for real-world clinical practice (Sadeqi et al, 2021). In a study conducted by Tripp et al (2024), interviews with nursing professionals revealed that nurses frequently struggle to retain information from their anatomy and physiology courses due to information overload.…”
Section: The Necessity Of Reforming the Human Anatomy Course In Nursi...mentioning
confidence: 99%
“…In this general context, the surgical integration of human anatomy lectures, which usually occur in the first and second years of the degree program, as well as the presence of in-depth human anatomy lectures in later years within integrated clinical courses, represent long-recommended goals for improving human anatomy teaching and learning, contextualizing its learning concerning the procedures and clinicaßl skills to be acquired by the student [9,10,[18][19][20][21][22]. Therefore, the clinical integration of anatomy is not new but has been established for many years in medicine and surgery Master's degree courses.…”
Section: New Curricular Integration In the Human Anatomy Course: Stud...mentioning
confidence: 99%
“…In particular, the Human Anatomy 1 module (focused on the locomotor system) is articulated with anatomy lessons interspersed with surgical lessons (given by orthopedists and neurosurgeons, who collaborate in subsequent modules of the anatomy course [8]) and is further implemented with a module on biological systems mechanics and biomechanics of the locomotor system (this module is carried out by an industrial bioengineering teacher). While the integration of anatomy with the clinical sciences is now well established in anatomy teaching [9,10], the integration with a bioengineering discipline is a major pedagogical innovation. Therefore, in this study, we investigated the educational value and the students' perceptions of the effectiveness and usefulness of this new type of integration compared to surgical integration.…”
Section: Introductionmentioning
confidence: 99%